Student Fundraising Practices as a Site of Exploitation: A Marxist Feminist Analysis of Gendered Labor in Campus Organizations - Martha Lazarsyta Daluri martha; Ahmad Ridwan; Putri Dwi Permata Indah; Refti Handini (MUWAZAH : jurnal kajian gender, 2026)
This study describes forms of student exploitation in campus fundraising activities through a Marxist feminist perspective. In practice, fundraising is often viewed as a learning activity and a means of developing students' interpersonal skills. However, the findings of this study indicate that behind this narrative lies a power relationship that places students, especially women, in exploitative positions of reproductive and emotional labor. This study used qualitative methods with a phenomenological approach to explore the lived experiences of three informants directly involved in fundraising activities. Data were collected through in-depth interviews, organizational observations, documentation studies, and literature reviews, then describes using thematic analysis techniques. The results of the study indicate four forms of exploitation: (1) a greater reproductive and emotional workload on female students; (2) a gender-based division of labor that places women in tasks related to body representation and public interactions; (3) structural pressures through hierarchies and organizational cultures that normalize uncompensated work; and (4) the commodification of women's bodies as a strategy for obtaining funds. This study concludes that the exploitation that occurs is the result of the intersection of campus capitalism and patriarchy that operate through organizational structures. These findings emphasize the importance of critiquing fundraising practices to make them more fair, transparent, and sensitive to gender issues.